The impact of distance learning on the attitudes of nursing students: An online survey study - Çağlar, Songül; Okuyan, Canan Birimoğlu (Acta Scientiarum. Health Sciences, 2023)
The COVID-19 pandemic has led to the transition to distance education in nursing education. However, Nursing students are not accustomed to learning through distance learning.This research aimed to determine the effect of distance education method on the attitudes of nursing students towards the profession during the COVID-19 pandemic. This research was cross-sectional in design. Data were collected with an online survey about distance education and the nursing profession through Google Forms in November 2020 and June 2021 at the nursing department. The students’ views on distance education were moderate (46.66±8.81), and their attitudes towards the nursing profession were good (86±13.86). There was no statistically significant relationship between scale scores. There was no statistically significant difference in terms of students’ grade levels, graduating from a distance education institution before, taking courses through distance education before the COVID-19 pandemic and clinical practice before the pandemic, and their attitudes towards both distance education and the nursing profession. Our study shows that the distance learning method does not affect students’ attitudes toward the nursing profession.